Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1994)
Table of Content : Francesco Clemente Francesco Clemente by Holland Cotter ; Fischli/Weiss Simulated Readymades by Fischli/Weiss by Boris Groys ; Günther Förg Günther Förg: Scenarist by Vocation by Max Wechsler Günther Förg’s Recent Paintings by David Rimanelli Damien Hirst Damien Hirst by Gordon Burn Decadent Geometry by Boris Groys ; Jenny Holzer No Ladders; Snakes: Jenny Holzer’s Lustmord by Joan Simon ; Rebecca Horn Vague Musings About the Work of Rebecca Horn by Gilbert Lascault A Draft in Kafka’s Bedroom. The Large Rebecca Horn Exhibition in Berlin by Werner Spies ; Sigmar Polke The Flip Side of Things by Bice Curiger The Unbearable Likeness of Being by Vik Muniz Boards and Borders by Jeff Perrone ; Going Back to Start, Perpetually: Playing the Nomadic Game in the Critical Reception of Art by G. Roger Denson ; A Matter of Times : On Flatness, Magic, Illusion, and Mortality by Dave Hickey ; Donald Judd, 1928 – 1994, Richard Serra
PARKETT IS TEN YEARS OLD Since Victorian times, Anglo-Saxon children have enjoyed playing Snakes and Ladders, a board game of ancient Indian origin. Scattered over about one hundred numbered squares are ladders that can speed one’s ascent into higher zones (and eventually, one hopes, to victory), and snakes that can bring about one’s downfall in a single unlucky move. It is a game of chance. Parkett is ten years old. A delight in metaphor originally inspired the name of the magazine—referring in German not only to the dance floor but also to the front rows of seats in a theater—and the various structuring rubrics, Les Infos du Paradis, Balkon, Cumulus; metaphor is once again the driving force behind our birthday issue. (editorial by publisher)
boek
Keywords: Clemente, Francesco; Horn, Rebecca; Polke, Sigmar; Holzer, Jenny; Hirst, Damien; Förg, Günther; Fischli, Peter; Weiss, David